Strategic Evolution of CSR: A Systematic Literature Review on Implementation, Impact, and Research Gaps - Vallensia Beuty Anastasya; Bunga Azahra Aulia (IJESM Indonesian Journal of Economics and Strategic Management, 2025)
This study presents a Systematic Literature Review (SLR) of recent research on Corporate Social Responsibility (CSR), focusing on its implementation across sectors, its strategic impact on organizational performance, and the identification of research gaps. Through a comprehensive review of 10 peer-reviewed articles published between 2018 and 2021, this study reveals that CSR has evolved beyond its philanthropic roots into a strategic instrument influencing customer loyalty, risk perception, corporate reputation, and financial outcomes. Key gaps identified include the lack of micro-level analysis, under-researched contexts in developing countries and SMEs, the symbolic versus substantive implementation of CSR, and the role of consumer skepticism and reputation as moderating variables. The study recommends future research to develop sector-specific frameworks, integrate digital tools such as big data, and enhance the empirical validation of CSR's causal impact on firm performance. Overall, CSR is recognized not just as "doing good" but as a contextualized, strategic, and authentic driver of sustainable corporate value.